Tracing New Landscapes in the Arena of Nanoparticle-Based Cancer Immunotherapy - Nadukkandy, Aisha Shigna; Ganjoo, Eshani; Singh, Ankit; Dinesh Kumar, Lekha (Frontiers in Nanotechnology, 2022)
Over the past two decades, unique and comprehensive cancer treatment has ushered new hopes in the holistic management of the disease. Cancer immunotherapy is one among which that is less debilitating and employs the immune system of the patient to boost targeting of the cancer cells. Significant advancements in the knowledge of immune surveillance in the twentieth century have led to the development of several types of immune therapy like monoclonal antibodies, cancer vaccines, immune checkpoint inhibitors, T-cell transfer therapy, or adoptive cell therapy (ACT) immune system modulators. Extensive research has established cancer immunotherapy to be a safe and effective method, improving survival and the quality of life in patients. Yet, numerous issues exist on the path of expanding and driving this therapy, with respect to site-specific delivery, resistance to immunotherapy, and escape of cancer cells from immune responses, preventing this method from developing into an ultimate medical treatment. Development in the field of nanotechnology has improved the therapeutic efficiency of the current treatment modalities. Being a unique field with advantageous properties like sizeable specific surface areas, targeted drug delivery, controlled surface and release chemistry, enhanced permeation and retention effect, nanotechnology offers the means to site-specific targeting. Nano carriers incorporating immunomodulatory agents can modulate the tumor microenvironment and initiate the functions of immune cells, thus enhancing antitumor immunity. Through this review, we discuss the current applications of nanoparticles in the development of ‘smart’ cancer immunotherapy agents like ACT, cancer vaccines, monoclonal antibodies, its site-specific delivery, and modulation of other endogenous immune cells, and highlights the vast possibilities of leveraging the coordinated and adaptive immune system of a patient to tackle the complexity of treating their unique disease conditions using nanotechnology, along with other future prospects. Robust validation of these techniques in the clinics has now paved the way to a better treatment option than the already existing procedures like chemotherapy and radiotherapy.